Peritumor tertiary lymphoid structures are associated with infiltrating neutrophils and inferior prognosis in hepatocellular carcinoma. (9th September 2022) - Zhang, Tianchen; Lei, Xinjun; Jia, Weili; Li, Jianhui; Nie, Ye; Mao, Zhenzhen; Wang, Yanfang; Tao, Kaishan; Song, Wenjie
Abstract: Background: The positive prediction of prognosis and immunotherapy within tertiary lymphoid structure (TLS) in cancerous tissue has been well demonstrated, including liver cancer. However, the relationship between TLS and prognosis in the peritumoral region of hepatocellular carcinoma (HCC) has received less attention. Few studies on whether TLS, as a typical representative of acquired immune cell groups, is associated with innate immune cells. The aim of this paper was to identify the prognostic role of peritumor TLS in HCC and to simply explore the relationship with neutrophils infiltration. Methods: This study included cancerous and paracancerous tissue from 170 patients after surgical resection of HCC. TLS was examined and identified by pathological H&E examination, and the impact on prognosis was further classified by determination of total TLS area. Immunohistochemical staining of CD15+ neutrophils was also performed on half of the cases. The obtained results were validated by external public database, as TLS has been widely shown to be tagged with 12 chemokines. Results: In peritumoral tissue, the TLS− group had better overall survival (OS) and disease‐free survival (DFS) outcomes compared with the TLS+ group. On the contrary, the intratumor TLS+ group showed better DFS outcomes. When further investigating the relationship between TLS area distribution and DFS, progressively worse prognosis was only found in the peritumor region with increasing TLS density (TLS− vs. TLSL vs. TLSH ). In addition, neutrophil infiltration increased in parallel with TLS density in the peritumoral region, which was not observed in the intratumoral region. Conclusions: TLS might have a dual prognostic role in different regions of HCC. The abundance of peritumoral TLS is an independent influence of DFS. The inconsistent correlation between neutrophils and corresponding TLS in different regions may indicate different pathways of immune aggregation and may serve as an explanation for the different prognosis of TLS, which needs to be specifically explored. Abstract : The positive role of tertiary lymphoid structure in tumor has received much attention, but peritumoral tertiary lymphoid structure in Hepatocellular Carcinoma has a different picture, which may be associated with neutrophil infiltration.